ANALISA KEANDALAN PENYULANG 20 KV DI JAKABARING SPORT CITY (JSC) DALAM MENGHADAPI ASIAN GAMES KE XVIII TAHUN 2018 - Putra, Dian Eka; Nurdiana, Nita; Simatupang, Roli (UNIVERSITAS MUHAMMADIYAH PALEMBANG, 2017)
The reliability of the 20 kV voltage distribution is a topic that has received widespread attention from the entire community including technicians, engineers, customers and others. This is because distribution reliability performance directly affects customers (consumers). In facing the implementation of the ASEAN GAMES to XVIII in Jakabaring Sport City (JSC) the provision of electrical energy required a good distribution system. The fundamental problems in the distribution of electrical power are on the quality, continuity and availability of electric power services to customers. The continuity of the supply of electrical energy to a buffer is greatly influenced by the reliability of the distribution system. Reliability describes a measure of the level of electricity supply service of the system greatly influenced by the configuration of the system, the installed security device and its protection system. To determine the reliability of a repeater in sports complex Jakabaring Sport City to meng ASEAN ASEAN GAMES to XVIII then set a reliability index that is the amount to compare the appearance of a distribution system. The reliability index is an indicator expressed in the probability scale. Index Reliability The commonly used load points include average load-out rate, average out time and average load-term duration. The widely used system reliability indexes include System Average Interruption duration Index (SAIDI) obtained by 0.00037802 min / mop and System Average Interruption Frequency Index (SAIFI) obtained value 0.00081712 times / mole and limited energy capacity hence required a standard where the efficiency of electricity can be taken into account.